Relationship between nocturia, depression, and cognitive function and the mediating effects of nutritional indexes in older adults: data from NHANES 2011–2014 - Xu, Yin; Wang, Xinmei; Wang, Guofeng; Wei, Wei; Li, Ning (Frontiers in Nutrition, 2025)
PurposeThis study evaluated the correlation between nocturia, depression, and cognitive function in older adults and the mediating effect of albumin and hemoglobin on this correlation.MethodsData on nocturia, depression, and cognitive function from the National Health and Nutrition Examination Survey 2011–2014 were analyzed by multiple logistic regression.ResultsThe digit symbol score (DSS) and 9-Item Patient Health Questionnaire (PHQ-9) scores were linearly and non-linearly correlated with nocturia risk (p < 0.05). Male/female-stratified analysis showed that animal fluency scores (AFS), DSS, and PHQ-9 scores were significantly correlated with the risk of nocturia in females (p < 0.05), and PHQ-9 scores were significantly associated with the risk of nocturia in males (p < 0.05). Albumin partially mediated the association of AFS, DSS, and PHQ-9 scores with nocturia risk in women and the relationship of PHQ-9 scores with nocturia risk in men. Hemoglobin partially mediated the relationship of AFS and DSS with nocturia risk in women and the association of PHQ-9 scores with nocturia risk in men.ConclusionNocturia is positively associated with depression and cognitive impairment in older adults, especially in women. Nutrition partially mediates the relationship between nocturia, depression, and cognitive function. Thus, improving nutrition may decrease the risk of nocturia in older adults.